A qualitative analysis of ostomy-related patient education videos on YouTube - Basım, Pelin; Arğun, Derya (NLM (Medline), 2021)
OBJECTIVE: To analyze the content, reliability, and quality of the most viewed YouTube videos targeting patients with ostomies intending to learn about ostomy care (OC). METHODS: Using the keywords "stoma care," "colostomy care," and "ileostomy care," researchers assessed the publicly visible English-language ostomy patient education videos available on YouTube. A total of 84 videos were independently analyzed by two physicians experienced in OC. Data on video characteristics, source, content, reliability, and quality were collected and recorded for each video separately. RESULTS: Of the 84 videos analyzed, 49 were classified as useful (58.33%) and 35 as misleading (41.66%). There were statistically significant differences between the groups in terms of the time elapsed since upload (P < .017), reliability (P < .001), comprehensiveness (P < .001), Global Quality Scale scores (P < .001), source (P < .001), and lecturer types (P < .011). The reliability, comprehensiveness, and Global Quality Scale scores were statistically higher for videos uploaded by universities, professional healthcare communities, and nonprofit physicians (P < .001). However, the popularity of the OC videos posted on YouTube was not related to their reliability, comprehensiveness, or quality. CONCLUSIONS: The open-access nature of the YouTube platform may impair patient education video quality and accuracy. YouTube may be an additional educational tool for OC, but clinicians need to be familiar with specific and reliable resources to guide and educate new patients with ostomies to achieve the best outcomes.
Keywords: Comprehensiveness; Content; Ostomy; Patient Education; Quality; Reliability; Self-Care; Video; YouTube